THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY & CAPITAL STRUCTURE ON COMPANY VALUE MODERATED PROFITABILITY AND FIRM SIZE - Jesslyn, Claresta; Budidarma, I Gusti Agung Musa (Ridwan Institute, 2024)
The purpose of this study is to analyze the influence of corporate social responsibility (CSR) and capital structure on company value with profitability and firm size as moderation variables. This study uses secondary data in the form of annual reports on the non-primary consumer, transportation, industrial, energy, health, and technology sectors listed on the Indonesia Stock Exchange in 2021 - 2023. The sample of companies studied is 154 companies with 462 data. The results show that the combination of independent variables, profitability as moderating variables, and the interaction of independently variable with moderation can affect the company's value by 71.79%. The significance values of CSRE, DAR, SIZE, CSR with firm size (CSRE x SIZE) and Capital Structure With Firm Size (DAR x SIZE) have values of 0.3724, 0.6024, 0,3405, 0.4334, and 0.6602 > 0.05. The combination of independently variables, profitability, and capital structures with firm sizes have values 0.1827, 0.3435, 0.4335, and 0.663, respectively. The impact of CSR on firm value is moderated by profitability, while firm size moderates the influence by capital structure. Furthermore, examining the role of different types of CRS activities or varying approaches to capital structure could provide insights into why certain strategies might succeed or fail in enhancing company value.